Self-Efficacy Improvement in Diabetes Mellitus Patients After Implementing Discharge Planning Based on Diabetes Self Care Management Education in Inpatient Room, dr. Haryoto Hospital, Lumajang - Putra, Yoga Bagus Santoso; Tursina, Hella Meldy (LPPM Universitas dr. Soebandi, 2024)
Diabetes (DM) is a chronic disease and is characterized by high blood sugar (glucose) levels, diabetes that is not well controlled, can cause various complications that endanger the patient. One of the pillars of DM management is health education. Health education can increase the self-efficacy of patients so that diabetes management can be optimized. Diabetes Self Management Education (DSME) is a diabetes management education and support program that can be a place for diabetes patients to get education, support development and maintain the behavior of diabetes patients. The management that will be implemented is implementing DSME-based discharge planning and measuring self-efficacy before and after the intervention. The design of this scientific paper uses a case study design. The subjects used were two patients with diabetes mellitus. Data analysis was carried out using descriptive analysis. Self-efficacy in (Mrs. S) patients who were given DSME-based charge planning increased from an initial self-efficacy score of 58 in the low category to 87 in the high category, Meanwhile the self-efficacy of (Mrs. P) patients who were given charge planning not based on DSME experienced a difference from the initial self-efficacy score of 54 in the low category to 59 in the low category. There is a change in self-efficacy in diabetes mellitus patients (Mrs.S) after implementing DSME-based discharge planning and there was no change in self-efficacy in diabetes mellitus patients (Mrs.P) who applied non-DSME-based discharge planning inpatient RSUD. dr. Haryoto Lumajang.